Verbal rules and rule-following: to the problem of environmental determination of behavior in modern behaviorism - Sergeev, Vsevolod N. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is dedicated to the problem of behavior which is shown in such a field of behavior sciences as behaviorology. Inquiries presented to the definition (objectivity, functionalism), the specificity of behavior research, the pattern of its determination and other issues are discussed. The formula of operational behavior is described, the variables are analyzed. A lot of attention is paid to specificity of variables correlation and namely to the concept of contingency. The main part tells about the number of methodological affirmations of radical behaviorism on the topic of verbal-governed behavior. The main attention is paid to taxonomy of verbal behavior namely including contingency-governed behavior and rule-governed behavior. There is a conceptual instrument completeness problem of radical behaviorism for explicating these types. It is indicated the functional role of the rule in the type of operation behavior. Moreover, it is mentioned the complexity of rulegoverned behavior identification in the line of other behavior acts. The analysis of rule essence is paid a lot of attention to.